Step by step 2007 Microsoft Office System (Microsoft Press, 2007)
Shows how to use Microsoft Office 2007's programs Access, Excel, Outlook, PowerPoint, and Word, providing step-by-step instructions and screen images, and includes a CD-ROM containing files for practicing the book's lessons, a searchable electronic version of the book, and other resources.